Family Separation, Reunification, and Intergenerational Trauma in the Aftermath of Human Trafficking in the United States - Juabsamai, Kamolwan ‘Juli’; Taylor, Ileana (Anti-Trafficking Review, 2018)
Family reunification is a complex part of a survivor’s journey; its processes long, arduous, and unassured. This article seeks to examine the intricacies of human trafficking and family separation in migration, and intergenerational trauma following family reunification. The authors apply theoretical frameworks and concepts established by literature on migration and trauma, and provide a case study to explain the implications of family separation that occurs during and after the survivor’s human trafficking experience. Written from the perspective of social service providers, this article also provides a look at life after trafficking and how the individual’s worldview is altered by the trauma endured, resulting in possible intergenerational transmission of trauma from parent to child. The article explains the family’s process of moving from crisis back to balance, and the need for adjustment and adaptation, flexibility and cohesion in finding resilience. Finally, the authors discuss family resiliency frameworks as empowering models for serving survivors of human trafficking and their families during the reunification process. With the appropriate support, families can move forward in their journey towards healing.